In Vitro and In Vivo Protective Effects of Lentil (Lens culinaris) Extract against Oxidative Stress-Induced Hepatotoxicity - Yeon-Seop Jung; So-Hee Lee; So Young Chun; Dae Hwan Kim; Byung Ik Jang; Man-Hoon Han; Syng-Ook Lee (Molecules, 2021)
Excessive oxidative stress plays a role in hepatotoxicity and the pathogenesis of hepatic diseases. In our previous study, the phenolic extract of beluga lentil (BLE) showed the most potent in vitro antioxidant activity among extracts of four common varieties of lentils; thus, we hypothesized that BLE might protect liver cells against oxidative stress-induced cytotoxicity. BLE was evaluated for its protective effects against oxidative stress-induced hepatotoxicity in AML12 mouse hepatocytes and BALB/c mice. H2O2 treatment caused a marked decrease in cell viability; however, pretreatment with BLE (25–100 μg/mL) for 24 h significantly preserved the viability of H2O2-treated cells up to about 50% at 100 μg/mL. As expected, BLE dramatically reduced intracellular reactive oxygen species (ROS) levels in a dose-dependent manner in H2O2-treated cells. Further mechanistic studies demonstrated that BLE reduced cellular ROS levels, partly by increasing expression of antioxidant genes. Furthermore, pretreatment with BLE (400 mg/kg) for 2 weeks significantly reduced serum levels of alanine transaminase and triglyceride by about 49% and 40%, respectively, and increased the expression and activity of glutathione peroxidase in CCl4-treated BALB/c mice. These results suggest that BLE protects liver cells against oxidative stress, partly by inducing cellular antioxidant system; thus, it represents a potential source of nutraceuticals with hepatoprotective effects.